2022
DOI: 10.3390/biom12020184
|View full text |Cite
|
Sign up to set email alerts
|

CNS-Sparing Histamine H3 Receptor Antagonist as a Candidate to Prevent the Diabetes-Associated Gastrointestinal Symptoms

Abstract: Among the histamine receptors, growing evidence points to the histamine H3 receptor as a pharmacological candidate to counteract the autonomic neuropathy associated with diabetes. The study aimed to evaluate the effect of PF00868087 (also known as ZPL-868), a CNS-sparing histamine H3 receptor antagonist, on the autonomic neuropathy of the intestinal tract associated with diabetes. Diabetes was induced in male BALB/c mice by a single high dose of streptozotocin (150 mg/kg). Colorectal specimens from control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…Our study first shows that neonatal hyperoxia significantly alters neuronal chemical coding in the myenteric plexus, increasing both ChAT + neurons and the SP immunoreactivity of nerve fibers while reducing the nNOS + neurons without changing the number of neurons per ganglion. This observation agrees with our previous results from a model of diabetes-induced intestinal injury [25]. In contrast, other models of colonic disorders have shown neuronal loss or different alterations in neuronal subpopulations [36,42,43].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study first shows that neonatal hyperoxia significantly alters neuronal chemical coding in the myenteric plexus, increasing both ChAT + neurons and the SP immunoreactivity of nerve fibers while reducing the nNOS + neurons without changing the number of neurons per ganglion. This observation agrees with our previous results from a model of diabetes-induced intestinal injury [25]. In contrast, other models of colonic disorders have shown neuronal loss or different alterations in neuronal subpopulations [36,42,43].…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in mucin production indicated by the observed reduction in PAS + -relative area is a marker of intestinal damage [24,36] and could be at least partially explained by a loss of goblet cells [24]. This finding is at variance with previous studies, which have reported an overproduction of mucins in rodent models of colonic injury as a reaction to dysmotility [25,37]. However, these animal models were designed to mimic intestinal disorders characterized by chronic inflammation and longlasting treatments, whereas ours exploits a different noxious stimulus applied for a short time to immature animals.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, a significant improvement in glucose tolerance was observed in experimental animals treated with the tested compounds. We suspected that this may be due to the fact that the experimental animals did not develop full obesity or to the effect of the tested ligands on H 3 R present in pancreatic β cells responsible for insulin secretion and blood glucose regulation [48].…”
Section: Discussionmentioning
confidence: 99%